2007
DOI: 10.1603/0022-0493(2007)100[1416:baiitp]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Bean α-Amylase Inhibitors in Transgenic Peas Inhibit Development of Pea Weevil Larvae

Abstract: This glasshouse study used an improved larval measurement procedure to evaluate the impact of transgenic pea, Pisum sativum L., seeds expressing a-amylase inhibitor (AI)-1 or -2 proteins on pea weevil, Bruchus pisorum L. Seeds of transgenic 'Laura' and 'Greenfeast' peas expressing alpha-(AI)-1 reduced pea weevil survival by 93-98%. Larval mortality occurred at an early instar. Conversely, in nontransgenic cultivars, approximately 98-99% of the pea weevils emerged as adults. By measuring the head capsule size, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…Investigations executed by Jackai et al (1997) showed that the insect pests of cowpea controlled by several other different forms of Bt crystal toxins and this basic information was further used by Adesoye et al (2008) and Bakshi et al (2011) to introduce Cry1Ab in cultivars (TVu 201,Ife Brown, and Cry1Ac genes in cultivar (Pusa Komal) in various cowpea genotypes, and their experiment results showed that the transgenes were carried in Mendelian fashion to the progenies which showed significant reduction of larvae survival and weight. These findings were confirmed by several other authors as the introduction of this gene in pea (Shade et al 1994;Schroeder et al 1995;Morton et al 2000;Sousamajer et al 2007), adzuki bean (Ishimoto et al 1996), and chickpea (Sarmah et al 2004;Ignacimuthu and Prakash 2006) conferred resistance against bruchid beetles.…”
Section: Transgenic Resistance To Insectssupporting
confidence: 78%
“…Investigations executed by Jackai et al (1997) showed that the insect pests of cowpea controlled by several other different forms of Bt crystal toxins and this basic information was further used by Adesoye et al (2008) and Bakshi et al (2011) to introduce Cry1Ab in cultivars (TVu 201,Ife Brown, and Cry1Ac genes in cultivar (Pusa Komal) in various cowpea genotypes, and their experiment results showed that the transgenes were carried in Mendelian fashion to the progenies which showed significant reduction of larvae survival and weight. These findings were confirmed by several other authors as the introduction of this gene in pea (Shade et al 1994;Schroeder et al 1995;Morton et al 2000;Sousamajer et al 2007), adzuki bean (Ishimoto et al 1996), and chickpea (Sarmah et al 2004;Ignacimuthu and Prakash 2006) conferred resistance against bruchid beetles.…”
Section: Transgenic Resistance To Insectssupporting
confidence: 78%
“…8 The gene encoding AI-1 has been transferred by genetic engineering from the common bean into other legumes, which have subsequently been protected against certain bruchids. 5,6,[9][10][11][12][13][14][15] For example, Shade et al 14 found that concentrations of 1.0% (w/w) AI-1 in genetically modified (GM) pea seeds were sufficient to provide complete resistance to their strains of C. chinensis and C. maculatus.…”
Section: Introductionmentioning
confidence: 99%
“…They are particularly vital for bruchids, which require α‐amylases to release not only energy, but also metabolic water . The gene encoding αAI‐1 has been transferred by genetic engineering from the common bean into other legumes, which have subsequently been protected against certain bruchids . For example, Shade et al .…”
Section: Introductionmentioning
confidence: 99%
“…αAI-1 is an α-amylase inhibitor and is toxic to bruchids because it inhibits their α-amylases, which are key enzymes in their digestion of long-chain carbohydrates. The gene coding for αAI-1 has been transferred into other legumes, including cowpea, which were subsequently protected against several bruchid species [1], [3]–[10]. Genetically modified (GM) cowpea expressing αAI-1 under the seed-specific promoter of the common bean phytohemagglutinin gene ( dlec2 ) is resistant to the two Callosobruchus spp.…”
Section: Introductionmentioning
confidence: 99%